Six Sigma project for reducing manual handling of materials in real manufacturing company : case study - Kochov, Atanas (Array, 2020)
This paper presents a case study that is focusing on the improvement of the process of materials handling in real manufacturing company. Before the implementation of this project, the company was in a concerning state of incidents and learning events towards the ergonomics, health and safety of the operators who manually handled materials as part of their daily activities. It was proposed to use the Six Sigma framework in order to improve the process or design new process for performing the task that included manual handling of materials. In this study, through selecting suitable Six Sigma framework, mapping the current process, setting key performance indicators and using various design tools and techniques, process improvement is proposed; it will solve the problem, increase ergonomics and safety, but also increase the speed of the process and reduce the cost of spilled materials that were manually handled.